Single-site trinuclear copper oxygen clusters in mordenite for selective conversion of methane to methanol - Grundner, Sebastian; Markovits, Monica A.C.; Li, Guanna; Tromp, Moniek; Pidko, Evgeny A.; Hensen, Emiel J.M.; Jentys, Andreas; Sanchez-Sanchez, Maricruz; Lercher, Johannes A. (Nature communications, 2015)
Copper-exchanged zeolites with mordenite structure mimic the nuclearity and reactivity of active sites in particulate methane monooxygenase, which are enzymes able to selectively oxidize methane to methanol. Here we show that the mordenite micropores provide a perfect confined environment for the highly selective stabilization of trinuclear copper-oxo clusters that exhibit a high reactivity towards activation of carbon–hydrogen bonds in methane and its subsequent transformation to methanol. The similarity with the enzymatic systems is also implied from the similarity of the reversible rearrangements of the trinuclear clusters occurring during the selective transformations of methane along the reaction path towards methanol, in both the enzyme system and copper-exchanged mordenite. Copper-exchanged zeolites with mordenite structure can mimic the active sites in particulate methane monooxygenase. Here, the authors show that mordenite micropores can stabilize trinuclear copper-oxo clusters that exhibit a high reactivity towards activation of carbon–hydrogen bonds in methane.